Social Safety Nets : Issues and Recent Experience. (International Monetary Fund, 1998)
The 14 papers that comprise this book, edited by Ke-young Chu and Sanjeev Gupta, provide a comprehensive review of the IMF's work on social safety nets. Part I provides a broad overview of the social concerns in structural policy and the basic work related to social safety nets. Part II deals with the design of social safety nets. Part III provides case studies on nine countries from different parts of the world.